USULAN RANCANGAN TATA LETAK FASILITAS DENGAN MENGGUNAKAN METODE FROM TO CHART - Yessi Maretha Miraningsih; Aurella Nur Amaria; Vinka Aurelia Putri; Yvonne Christy Julyandini; Hery Murnawan (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2023)
Facility layout is an important thing that must be managed effectively and efficiently in order to produce optimal material handling costs. UD Karya Abadi is a manufacturing industry engaged in the manufacture of pans. The long-distance of materials movement is an obstacle during the production process. The distance of the material in carrying out the transfer will affect the total costs required in the production process. Facility layout design is carried out by paying attention to material handling distances and relationships between departments. The from to chart method is used to determine the smallest number of product moments that can be designed in an industrial layout. This research resulted in a decrease in product moment of 2840.181 from 4769.059 to 1928.878. The decrease in the product moment means that the material movement becomes smaller, so it can increase production capacity due to the smaller operator movements. This research resulted in a proposed layout for a new production facility and lowered material handling costs.Keywords: From to Chart, Layout, UD Karya Abadi